Producción de leche de vacas mestizas del Sistema Doble Propósito en el municipio de Arauca (2012)
Milk production and lactation length are parameters to find out the amount of milk produced by cows and per farm. There were compared by the farm milk production variables: days of lactation (DILAC), daily milk (KDIA) and total milk per lactation (KTOT) of 95 lactating crossbred cows from five farms in the town of Arauca. Linear procedures there were used GLM of SAS. Comparison of means was done by Tukey test. The estimated average was (KTOT) 521.1 ± 254.8 kilos with a variation of 42.0%, the mean for DILAC was 253.4 ± 85.7 days with 29.1% of variation. The farm was a significant variation factor (p < 0.01) for features and KTOT KDIA and did not affect (p < 0.05) the DILAC. The year of birth of the offspring had a significant effect (p < 0.01) on DILAC, had no effect (p < 0.05) on daily production and approached the 5% probability (p = 0.06) in total. The parity only affected significantly (p < 0.05) total milk production, while the breed of cow on the farm affected (p < 0.05) days in milk production and total milk (p < 0.01). We conclude that environmental factors analyzed: farm, year of birth and parity and the effect of racial group affected the milk production parameters studied.